Investigation of Luromarin Efficacy on Mice with Experimental Tick-Borne Encephalitis - N. V. Krylova; G. N. Leonova; A. M. Popov; A. A. Artyukov; E. P. Kozlovskaya (Антибиотики и Химиотерапия, 2020)
Oral use of Luromarin, extracted from sea algae Zostera asiatica, was efficient In protection of mice from lethal infection induced by highly pathogenic strain of TBE virus, by extending their average lifespan. Luromarin demonstrated potentiating action in combination with ribavirin and cycloferon.